Modelling of Gas Metal Arc Welding Process on Angular Distortion of T Joint - Swanson1, P.; Effendi, S.; Nizam, Md (Journal of Advanced Manufacturing Technology (JAMT), 2014)
Gas Metal Arc Welding (GMAW) is one of the widely used joining technologies in metal fabrication. The quality of a joint is greatly influenced by the selection of GMAW process parameter settings. One of the quality issues faced in welding is angular distortion. This research focused on angular distortion issues due to welding that happened in a local car chassis manufacturing company. The distortion resulted in high reject and rework rate. Conventional approach to optimize the welding process parameter in solving this issue has yet to result in significant improvement. The aims of this work is to study the influence of welding speed, welding angle, welding current and the resultant angular distortion using Response Surface Methodology (RSM) approach. The experiment was carried out using robotic welding manipulator AVII V6, OTC DAIHEN. Deposition of fillet weld on T joint arrangement was performed on test piece made of low carbon steel SAPH S45C. The angular distortion was measured using Olympus STM stereo measuring microscope and the data analysis was carried out using Design Expert version 8.0.7. The result indicated that interaction between welding angle and speed is the most significant factors that influence the angular distortion and the relationship between the evaluated input parameters and the angular distortion can be modeled using 2Factor Interaction model.